Effects of e-CRM: experience-based marketing, digital communications on Garuda Indonesia Airlines, brand trust, and repurchase intention - Widarto Rachbini; Diana Anggraeni; Ahmad Badari Burhan; Harimurti Wulandjani; Emi Rahmawati (Penerbit Universiti Kebangsaan Malaysia, 2024)
The research studied the effects of electronic customer relationship management (e-CRM), digital communications, and experience-based marketing on brand trust and repurchase intention in Garuda Indonesia Airlines, the National Flag Carrier of Indonesia. The primary data was collected through an online questionnaire distributed from March 2022 to July 2022. Purposive sampling was used to select passengers who had previously used the services of Garuda Indonesia Airlines. Out of the distributed online questionnaires, 270 respondents met the sampling criteria and responded to the questionnaire. Structural Equation Model (SEM), supported by LISREL software, was employed as the data analysis technique. The results show empirical findings on the significant effects of e-CRM, digital communications, and experience-based marketing on brand trust. The research also reveals that e-CRM and the airline's brand trust have positive and significant effects on repurchase intention. Based on the obtained data, this research provides several valuable managerial implications for Garuda Indonesia, one of the largest airline companies in Indonesia. In general, the research yields four significant implications, including the optimization of Instagram usage, the utilization of social media as an e-CRM tool, experience-based marketing through brand collaboration, and the implementation of thematic campaigns. The other findings indicate that brand trust plays a crucial role in reducing risk and uncertainty. The majority of passengers surveyed in this study expressed that Garuda Indonesia Airlines demonstrates a strong commitment to fulfilling passengers' needs during flights, reflecting a high level of trust in the brand. This positive perception carries significant implications, as it encourages passengers to choose Garuda Indonesia Airlines for future travel. Moreover, it motivates passengers to willingly recommend the airline to their friends and family. Additionally, the research findings reveal that passengers actively seek up-to-date information on flight tickets, programs, events, and schedules. Future research should consider studying low-cost carrier airlines (LCC) using a similar framework, focusing on respondents from Generation Z, to obtain diverse research results and contribute to the scientific research and literature on marketing and communication.